STUDI PENYADAPAN GETAH PINUS CARA BOR DENGAN STIMULAN H2SO4 - Mody Lempang (BRIN Publishing, 2017)
In general, pine resin yield is affected by various factors i.e. pine tree species, growing environment and tapping method. This paper studies pine resin tapping yield by drilling method using H₂SO₄ stimulant. Tapping point is designed in the depth of 4, 6 and 8 cm and sloping 25°. Three stimulant concentrations (0, 15%, 30%) were brushed in the tapping point and the treatments were repeated 10 times. Experimental design based on 3 × 3 factorials in completely randomized design. The first factor is the depth of drilling holes, the second factor is the concentration of H₂SO₄ stimulant used and repetition of 10 times. Pine resin yields were analyzed using analysis of variance and further test was conducted by honestly significant difference test. Results show that tapping pine by drilling and stimulant addition produced pine resin between 15.5 to 109.3 g / tree / collection (56.3 g / tree / collection on average) or between 2.6 to 18.2 g / tree / day (9.4 g / tree / day on average). Pine resin yield is significantly influenced by drilling hole depth and H₂SO₄ stimulant concentrations. The deeper the drilling hole, the more pine resin yield, and the higher the concentration of H₂SO₄ stimulant the higher pine resin yield. Pine resin yield of 8 cm tapping depth is 65.96% higher than 4 cm tapping depth, and 30% H₂SO₄ improved the yield by about 56.45%. The largest pine resin yield is achieved from tapping point of 8 cm depth and 30% H₂SO₄ that yiled about 90.7 g / tree / collection in average.